HEGEMONI POLITIK DALAM GERAKAN DA’WAH MUHAMMAD BIN ABDUL WAHAB - Irhamdi, M. (Universitas Islam Negeri Mataram, 2017)
Da’wah is an effort to invite someone to a favor, but not all da’wah activities can be accepted by the community. In this case the author was interested to see the notion of Muhammad Bin Abdul Wahab who have big ambitions to do da’wah because a movement viewed Islamic practices in the area of his birth no longer rests on a familiar whence are practices and even worship him have reached the point of shirk. As for political hegemony Abdul Wahab are symbiosis mutualism cooperation do with Ibn Saud, in order that the da’wah activities of his running smoothly without the presence of an attitude of resistance and rejection by societies. The existence of political hegemony Abdul Wahab certainly psychologically brings the impact of fear on society because it could not afford to reject the teachings of Muhammad ibn Abdul Wahab who got permission and support by Ibn Saud. So due to the existence of the authority of Ibn Saud in these areas so that whatever was said to the King, then a necessity for the people to accept the decision of the King.